Multimorbidity patterns and cognitive frailty in adults aged over 50 years: China perspective - Zhu, Jiehua; Ren, Chenxi; Hu, Tingjun; Jin, Jun; Guo, Qihao (Frontiers in Public Health, 2025)
IntroductionThe multimorbidity underlying in cognitive frailty remain poorly understood.MethodsA cross-sectional study was performed in non-dementia Chinese aged over 50 years, Cognitive frailty (cognitive impairment and slow gait [SG]). Cardiovascular and cerebrovascular diseases (CCVD) (heart disease, type 2 diabetes, hypertension, hyperlipidemia and cerebral infarction). Continuous variables were evaluated using one-way analysis of variance (ANOVA). Categorical variables were assessed using the chi-square test. Pairwise comparisons were performed using the Bonferroni-corrected column proportion test (z-test). Multiple logistic regression analysis was conducted to identify factors associated with cognitive frailty.ResultsA cross-sectional study included 571 males and 1,182 non-demented Chinese aged ≥50 years, categorized into 6 groups: normal, SG, subjective cognitive decline alone (SCD-A), mild cognitive impairment alone (MCI-A), subjective cognitive decline with slow gait (SCD-SG), and mild cognitive impairment with slow gait (MCI-SG). Cognitive frailty was defined as cognitive impairment plus SG. Walking speed and hand grip strength were lower in SG, SCD-SG, and MCI-SG groups (p < 0.05). SCD-SG and MCI-SG groups had higher prevalence of ≥3 chronic conditions (p < 0.05); SCD-SG and MCI-SG groups showed higher ≥3 CCVD (9.5, 9.2%; p < 0.05) in female. SCD-SG group had higher risk of 1–2 chronic conditions (OR = 1.81, 95%CI = 1.06–3.07) and ≥3 chronic conditions (OR = 3.79, 95%CI = 1.96–7.36).ConclusionCognitive frailty in Chinese aged ≥50 years increases risk of ≥3 chronic diseases, with SCD-SG group at highest risk, highlighting the need for attention to cognitive frailty and multimorbidity.